SEJARAH TERBENTUKNYA DESA BANGKALI KECAMATAN WATOPUTE KABUPATEN MUNA : 1976-2017 - Ahmad Jaya; Fatma Fatma (Jurusan Ilmu Sejarah Fakultas Ilmu Budaya Universitas Halu Oleo, 2019)
This study aims to describe the history of the formation of Bangkali Village, Watopute District, Muna Regency. The method used in the study was the historical method developed by Kuntowijoyo through five stage of work, namely: (1) Topic Selection, (2) Collection of cources, (3) references verification (critical sources throught external and internal critical sources) and (4) sources Interpretation (analysis and synthesis) and (5) Historiography (historycal writing). The lliterature review in this study consisted of the conceptual framework and the theoretical framework. The conceptual framework used the concept of regional expansion, the concept of rural history, and the concept of village and village governance. The theoretical framework used elite circulation theory. The findings of the research showed that: (1) Bangkali Village was formed due to consideration of the area and population density conditions which were sufficient to be expanded. (2) The process of establishing Bangkali Village, namely: (a) It was begun with government policy that each hamlet far from the parent village must be divided so that it is easy in the administrative process. (b) Support from the village community and community leaders to immediately propose the division of the village to the regional government. Then, Bangkali Village was formed on April 15th, 1976 through decree number 27 of 1976 concerning the division of villages in Wali Village. (3) The development of Bangkali Village in 1976-2017 in general showed a fairly good development in the fields of politics, general government, infrastructure, and economy. Keyword: History, Background, Process and Development